A Bibliometric Review of the Dam Construction Impact - Fata, Nurul; Ikhsan, Jazaul (Semesta Teknika, 2024)
Dams are crucial constructions for managing water supplies. However, the detrimental environmental effects of dam development have also drawn criticism. The influence of dam construction over the past fourteen years and new research trends are included in this study.  This study aims to determine how many papers have been produced, how productive researchers are, and chart the evolution of dam impact publications. The analysis showed that 1312 publications related to the topic discussed were generated. The findings demonstrated that engineering and environmental studies were the main focus of research trends concerning the effects of dam development. This study provides an overview of the trends in the direction of existing literature for future research, and evaluation of research topics through existing topic clusters. China, the USA and the United Kingdom are the three leading countries in dam construction impact research in terms of publications.